Artificial Intelligence and Its Impact on Society: Opportunities and Challenges - Jagga, Ankit (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Artificial Intelligence (AI) has emerged as one of the most transformative technological developments of the modern era. From automated decision-making systems to intelligent virtual assistants, AI technologies are increasingly integrated into everyday life. While these systems offer significant benefits in terms of efficiency, productivity, and innovation, they also raise important social, ethical, and economic concerns. Sociologists and technology scholars have begun examining how AI influences employment structures, decision-making processes, privacy, and social inequality. This paper explores the social implications of artificial intelligence by reviewing existing literature and analyzing how AI technologies shape contemporary societies. The study highlights both the opportunities provided by AI and the challenges it creates for social institutions, including labor markets, governance systems, and interpersonal relationships. The paper concludes that while AI has the potential to improve human welfare, careful regulation and ethical considerations are necessary to ensure that technological advancements benefit society as a whole.